2013
DOI: 10.1037/a0033003
|View full text |Cite
|
Sign up to set email alerts
|

The role of suppression in resolving interference: Evidence for an age-related deficit.

Abstract: Difficulty with memory retrieval is a salient feature of cognitive aging and may be related to a reduction in the ability to suppress items that compete for retrieval. To test this hypothesis directly, we presented a series of words for shallow coding that included pairs of orthographically similar words (e.g., ALLERGY and ANALOGY). After a delay, participants solved word fragments (e.g., A _ L _ _ GY) that resembled both words in a pair but could only be completed by one. We measured the consequence of having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
74
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 66 publications
11
74
1
Order By: Relevance
“…Despite this, older adults still recollected fewer changes, and this partly explained why older adults showed proactive interference in their recall, but younger adults did not. Older adults' greater susceptibility to interference shown in that study is similar to results shown in other interference paradigms (e.g., Hasher & Zacks, 1988;Jacoby, Debner, & Hay, 2001;Healey, Hasher, & Campbell, 2013). However, these results from Wahlheim (2014) showed that in situations involving episodic change, this deficit can be partly explained by differences in the ability to detect and recollect changes.…”
Section: Adult Age Differences In Event Perception and Memory For Changesupporting
confidence: 54%
See 2 more Smart Citations
“…Despite this, older adults still recollected fewer changes, and this partly explained why older adults showed proactive interference in their recall, but younger adults did not. Older adults' greater susceptibility to interference shown in that study is similar to results shown in other interference paradigms (e.g., Hasher & Zacks, 1988;Jacoby, Debner, & Hay, 2001;Healey, Hasher, & Campbell, 2013). However, these results from Wahlheim (2014) showed that in situations involving episodic change, this deficit can be partly explained by differences in the ability to detect and recollect changes.…”
Section: Adult Age Differences In Event Perception and Memory For Changesupporting
confidence: 54%
“…12, 2017; we hypothesized that successful change recollection would be associated with better recall of Day 2 activity features and lower rates of intruding Day 1 features. Based on earlier findings showing that older adults are more susceptible to interference effects (Healey, Hasher, & Campbell, 2013;Jacoby, Debner, & Hay, 2001;Wahlheim, 2014), we expected older adults to show a differential deficit for recall of changed activities, which would partly reflect a change recollection deficit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another, non-mutually exclusive possibility is that older adults' retrieval control processes are weaker than even those of young adults under DA at retrieval. Indeed, older adults show greater susceptibility to interference (Ikier, Yang, & Hasher, 2008) and a reduced ability to resolve interference at retrieval compared to young adults (Healey, Hasher, & Campbell, 2013). Also, older adults show retrieval impairments that are not typically observed in young adults under DA, such as higher rates of false recognition for associates of target words (Budson, Sullivan, Daffner, & Schacter, 2003), and a greater influence of misleading stimuli at retrieval (Jacoby, Bishara, Hessels, & Toth, 2005), suggesting that retrieval in older adults may be affected by factors other than a simple reduction of attentional resources.…”
Section: Discussionmentioning
confidence: 99%
“…These are then available to and compete for the focus of attention at later retrieval, and neural evidence also suggests that older adults' re-activated memory representations are less stimulus-specific than young adults' (St-Laurent et al, 2014), allowing further opportunity for competition and interference. Across multiple trials, especially with related stimuli, these effects may "snowball" to further increase age differences, as during retrieval young adults suppress related competitors more efficiently than do older adults (Healey et al, 2013).…”
mentioning
confidence: 99%